Analisis Hukum Perdata Internasional dalam Pernikahan WNI dengan WNA di Luar Negeri - Agustin Riyanti, Dwi; Aulia Akip Saputri, Bunga; Tri Anggraeni, Selvi; Gillang Anuggrah, Alldo; Mul Erowati, Eti (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Marriages between Indonesian citizens (WNI) and foreign citizens (WNA) abroad are increasingly common along with increasing global mobility. However, this phenomenon also presents complex legal challenges, especially related to marriage procedures, legal recognition, and family rights. This research aims to analyze International Private Law in the context of marriages between Indonesian citizens and foreigners abroad, as well as evaluating the challenges faced by inter-country couples and the legal solutions available. The research method used is a qualitative approach with descriptive-analytic techniques, which includes in-depth interviews with legal experts and Indonesian-WNA couples, as well as literature studies. The research results show that International Private Law plays an important role in providing legal certainty and protection for couples, through regulating marriage procedures, recognizing marital status, and resolving disputes. Despite challenges in legal recognition and differences in legal systems, applying the principles of Private International Law can help reduce uncertainty and protect the rights of couples. It is hoped that this research can provide a deeper understanding of the importance of International Private Law in regulating mixed marriages between countries.